Blood heavy metal levels in children with attention deficit hyperactivity disorder: an unsolved enigma - Sehgal, Rachna; Gulati, Sheffali; Gupta, Yogendra K.; Sapra, Savita; Pandey, Ravinder M.; Kabra, Madhulika (International Journal of Contemporary Pediatrics, 2020)
Background: The role of heavy metals in the etio-pathogenesis of attention deficit hyperactivity disorder (ADHD) is a burning enigma. The available studies with discordant results are from different geographical localities with different monitoring, regulations and sociocultural backgrounds. The differential association of heavy metals with ADHD severity and phenotypes has not been adequately examined. Also, there are concerns about laboratory quality control. Therefore, the present case control study was formulated. Methods: Thirty children with ADHD diagnosed by DSM IV criteria and thirty group age matched controls were enrolled. Detailed perinatal, past, developmental and possible exposure history to various heavy metals was taken. Severity of ADHD was assessed using ConnersTM Parent reporting questionnaire. Blood level of metals was estimated by inductively coupled plasma- atomic emission spectroscopy (ICP-AES). Results: The mean blood lead, mercury, cadmium, arsenic, zinc were comparable in children with ADHD and group age matched controls. The mean blood lead, mercury and cadmium levels in study population was higher than found in studies from developed countries. Elevated arsenic, mercury and cadmium were found in both cases and controls. Blood zinc correlated significantly with inattention T score and blood mercury with hyperactivity-impulsitivity T score of Conners parent rating scale. Blood cadmium was present in greater proportion of predominant hyperactive-impulsive type patients. Conclusions: Zinc deficiency correlates with inattention; cadmium and mercury toxicity correlate with hyperactivity. Mean blood levels of heavy metals is elevated in a substantial proportion of study population. So, there is an urgent need for sensitization and environmental control.